Are long-lasting insecticide-treated bednets and water filters cost-effective tools for delaying HIV disease progression in Kenya? - Verguet, Stéphane (Glob Health Action, 2015)
BACKGROUND: Co-infection with malaria and other infectious diseases has been shown to increase viral load and accelerate HIV disease progression. A recent study in Kenya demonstrated that providing long-lasting insecticide-treated bednets (LLIN) and water filters (WF) to HIV-positive adults with CD4 >350 cells/mm(3) significantly reduced HIV progression. DESIGN: We conducted a cost analysis to estimate the potential net financial savings gained by delaying HIV progression and increasing the time to antiretroviral therapy (ART) eligibility through delivering LLIN and WF to 10% of HIV-positive adults with CD4 >350 cells/mm(3) in Kenya. RESULTS: Given a 3-year duration of intervention benefit, intervention unit cost of US$32 and patient-year ART cost of US$757 (2011 US$), over the lifetime of ART patients, in Kenya, we estimated the intervention could yield a return on investment (ROI) of 11 (95% uncertainty range [UR]: 5–23), based on a cost of about US$2 million and savings in ART costs of about US$26 million (95% UR: 8–50) (discounted at 3%). Our findings were subjected to a number of sensitivity analyses. Of note, deferral of time to ART eligibility could potentially result in 3,000 new HIV infections not averted by ART and thus decrease ART cost savings to US$14 million, decreasing the ROI to 6. CONCLUSIONS: Provision of LLIN and WF could be a cost-saving and practical method to defer time to ART eligibility in the context of highly resource-constrained environments experiencing donor fatigue for HIV/AIDS programs.